PENGARUH FAKTOR KOMPETENSI TERHADAP PRODUKTIVITAS KERJA KARYAWAN MEDIA FURNITURE PT.PANGGUNG ELEKTRIK CITRABUANA - Agus Wahyudi Agus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Abstract The purpose of this study is to analyze how knowledge, skills, work experience, and behavior influence the productivity of employees in Media Furniture at PT. Panggung Electric Citrabuana, while also determining which of these factors has the greatest effect. The research utilizes descriptive analysis, multiple linear regression, assessment of the instruments, verification of classical assumptions, hypothesis testing (both simultaneous and partial), along with the calculation of correlation and determination coefficients. The results reveal that the factors of competency—knowledge, skills, work experience, and behavior—play a crucial role in boosting employee productivity. This conclusion is reinforced by statistical results indicating that each variable has a p-value of 0. 05 or lower, suggesting that all factors positively and significantly impact productivity. Consequently, the original hypothesis has been validated. Among these elements, behavior stands out as the most crucial, as indicated by its highest beta coefficient relative to the other factors. This highlights the importance of behavior in enhancing employee performance, thereby supporting the study's second hypothesis.